A Global MetaUniversity to Lead by Design to a Sustainable Well-Being Future - Costanza, Robert; Kubiszewski, Ida; Kompas, Tom; Sutton, Paul C. (Frontiers in Sustainability, 2021)
The COVID19 pandemic has revealed deep, ingrained problems with higher education, but also opportunities for positive transformation. In the post-COVID world, education at all levels has the chance to become: (1) universally available at low cost; (2) focused on developing competencies, (3) empowering fulfilling lives, not merely job training; and (4) engaged with communities to solve real-world problems. Achieving this will require overcoming the mass production model of higher education by utilizing the full potential of the Internet in creative ways balanced with face-to-face solutions-based integrated learning, research, and outreach agenda. Building a global collaborative consortium of universities and other educational institutions can move this agenda forward. We describe how this ‘MetaUniversity’ could be structured and how it would serve to advance this agenda and lead the way to a sustainable well-being future for humanity and the rest of nature.